Chemokine (C‐X‐C motif) ligand 1 and CXCL2 produced by tumor promote the generation of monocytic myeloid‐derived suppressor cells. Issue 12 (8th November 2018) - Shi, Huifang; Han, Xiaoqing; Sun, Yingying; Shang, Chao; Wei, Min; Ba, Xueqing; Zeng, Xianlu
Abstract : Accumulation of myeloid‐derived suppressor cells (MDSC) in tumor‐bearing hosts is a hallmark of tumor‐associated inflammation, which is thought to be a barrier to immunosurveillance. Multiple factors secreted by tumor cells and tumor stromal cells are reported to be involved in promoting the expansion of MDSC. Herein, we showed that s.c. inoculation of tumor cells and i.v. injection of tumor‐conditioned medium increased the number of MDSC. Subsequent investigation elucidated that chemokine (C‐X‐C motif) ligand 1 (CXCL1) and CXCL2, which were originally characterized as the chemokines of neutrophils, specifically promoted the expansion of monocytic MDSC (mo‐MDSC), a subtype of MDSC, in the presence of granulocyte‐macrophage colony‐stimulating factor. Depletion of CXCL1 or CXCL2 in B16F10 cells or in B16F10‐bearing mice noticeably decreased the generation of mo‐MDSC in bone marrow. Moreover, we found that, in addition to the tumor cells, tumor‐infiltrated CD11b + myeloid cells also expressed CXCL1 and CXCL2. Furthermore, CXCL1‐ and CXCL2‐induced increase of mo‐MDSC was not correlated with chemotaxis, proliferation or apoptosis of mo‐MDSC. These findings show a novel role of CXCL1 and CXCL2 in promoting mo‐MDSC generation by favoring the differentiation of bone marrow cells in tumor‐bearing conditions, which suggests that inhibition of CXCL1 and CXCL2 could decrease mo‐MDSC generation and improve host immunosurveillance. Abstract : Our results elucidated that CXCL1 and CXCL2, which were originally characterized as chemokines of neutrophils, specifically promoted the expansion of mo‐MDSC, a subtype of MDSC, in the presence of GM‐CSF. Moreover, we found that, in addition to the tumor cells, tumor‐infiltrated CD11b+ myeloid cells also expressed CXCL1 and CXCL2. Therefore, inhibition of CXCL1 and CXCL2 could decrease mo‐MDSC generation and improve host immunosurveillance.